Analysis of faith. Issue 9 (7th June 2018) - Rettler, Bradley
Abstract: In recent years, many philosophers of religion have turned their attention to the topic of faith. Given the ubiquity of the word "faith" both in and out of religious contexts, many of them have chosen to begin their forays by offering an analysis of faith. But it seems that there are many kinds of faith: religious faith, non‐religious faith, interpersonal faith, and propositional faith, to name a few. In this article, I discuss analyses of faith that have been offered and point out the dimensions along which they differ.